Microstructure and hardness of diffusion bonded sialon-AISI 420 martensitic stainless steel - Ibrahim, N.N.M. (Trans Tech Publications Ltd, 2014)
The objective of this work was to examine the microstructure, interdiffusion of elements, and hardness of joining sialon to AISI 420 martensitic stainless steel using diffusion bonding process. These materials were diffusion bonded at 1200Â°C for one hour under 20 MPa in a vacuum of 2.1Ã10-6 Torr. The microstructural analyses showed that joining sialon to nitrided steel produced thinner reaction layers and no gap or crack were formed on the sample. Gaps were produced in joining sialon to as-received steel. From the elemental analyses, alumina and iron silicides were formed at the interface layer of sialon/as-received steel joint. Alumina and smaller amount of silicides were detected at the interface layer of sialon/nitrided steel joint. Diffusion layer and parent steel of the sialon/nitrided steel joining contained nitrides. The hardness test across the joints indicated that reaction layers possessed intermediate hardness between sialon and steel. The layers contributed to ductility of the joint that help to attain the joint. Â© (2014) Trans Tech Publications, Switzerland.